Combined effects of leaf litter and soil microsite on decomposition process in arid rangelands - Carrera, Analía Lorena (2013)
The objective of this study was to analyze the combined effects of leaf litter quality and soil properties on litter decomposition and soil nitrogen (N) mineralization at conserved (C) and disturbed by sheep grazing (D) vegetation states in arid rangelands of the Patagonian Monte. It was hypothesized that spatial differences in soil inorganic-N levels have larger impact on decomposition processes of non-recalcitrant than recalcitrant leaf litter (low and high concentration of secondary compounds, respectively). Leaf litter and upper soil were extracted from modal size plant patches (patch microsite) and the associated inter-patch area (inter-patch microsite) in C and D. Leaf litter was pooled per vegetation state and soil was pooled combining vegetation state and microsite. Concentrations of N and secondary compounds in leaf litter and total and inorganic-N in soil were assessed at each pooled sample. Leaf litter decay and soil N mineralization at microsites of C and D were estimated in 160 microcosms incubated at field capacity (16 month). C soils had higher total N than D soils (0.58 and 0.41mg/g, respectively). Patch soil of C and inter-patch soil of D exhibited the highest values of inorganic-N (8.8 and 8.4 g/g, respectively). Leaf litter of C was less recalcitrant and decomposed faster than that of D. Non-recalcitrant leaf litter decay and induced soil N mineralization had larger variation among microsites (coefficients of variation= 25 and 41%, respectively) than recalcitrant leaf litter (coefficients of variation= 12 and 32%, respectively). Changes in the canopy structure induced by grazing disturbance increased leaf litter recalcitrance, and reduced litter decay and soil N mineralization, independently of soil N levels. This highlights the importance of the combined effects of soil and leaf litter properties on N cycling probably with consequences for vegetation reestablishment and dynamics, rangeland resistance and resilience with implications for management and conservation.